CONCEPTUAL AND FRAME ORGANIZATION OF THE FAMILY OF WORDS WITH THE PEAK OF PR - T V Levanova (Rusistika (Moskva. Online), 2017)
The author of the article suggest a conceptual and frame approach to the description of a family of words. The author study the concept of PR. The concept of PR includes 114 derived words. All vocabulary is structured according to the levels of logical classification. The upper tier of the superframe includes semes: 1) the material world; 2) the organic world; 3) the person; 4) a person in society; 5) work activity rights. On the lower tier, we select 6 subframes: 1) action, PR activity; 2) association, the structure that carries out the activities of public relations; 3) characteristics, inherent, characteristic for PR; 4) event, PR event; 5) the situation of PR; 6) relations in the field of PR.